Antarctic heterotrophic bacterium Hymenobacter nivis P3T displays light‐enhanced growth and expresses putative photoactive proteins. Issue 2 (15th November 2018) - Terashima, Mia; Ohashi, Keisuke; Takasuka, Taichi E.; Kojima, Hisaya; Fukui, Manabu
Summary: Hymenobacter nivis P3 T is a heterotrophic bacterium isolated from Antarctic red snow generated by algal blooms. Despite being non‐photosynthetic, H. nivis was dominantly found in the red snow environment that is exposed to high light and UV irradiation, suggesting that this species can flourish under such harsh conditions. In order to further understand the adaptive strategies on the snow surface environment of Antarctica, the genome of H. nivis P3 T was sequenced and analyzed, which identified genes putatively encoding for light‐reactive proteins such as proteorhodopsin, phytochrome, photolyase and several copies of cryptochromes. Culture‐based experiments revealed that H. nivis P3 T growth was significantly enhanced under light conditions, while dark conditions had increased extracellular polymeric substances. Furthermore, the expression of several putative light‐reactive proteins was determined by proteomic analysis. These results indicate that H. nivis P3 T is able to potentially utilize light, which may explain its dominance on the red snow surface environment of Antarctica. Originality‐significance statement: The role of proteorhodopsin in heterotrophic bacteria is not well‐characterized, as only a handful of proteorhodopsin‐harbouring isolates were shown to have a light‐enhanced phenotype through culture‐based experiments to date. This is the first study that demonstrates light‐stimulated growth and protein expression evidence of photoactive proteins for a non‐marine psychrophile and for a member of the genus Hymenobacter . It is also the first study that provides comprehensive proteome information for this genus. This study presents significant results in understanding the adaptive mechanism of a heterotrophic non‐photosynthetic bacterium thriving on the snow surface environment of Antarctica as well as demonstrating the role of light‐utilization in promoting growth, possibly through proteorhodopsin.